Pengaruh Literasi Kewirausahaan dan Kemampuan Berpikir Kreatif Terhadap Minat Mahasiswa Untuk Berwirausaha Pada Mahasiswa Jurusan PIPS dan PMIPA Angkatan 2019 Universitas Jambi - Mohd Rozak, Rezik; Muazza, Muazza; Yaldi, Destri (Jurusan Pendidikan IPS FKIP UNJA, 2023)
This study aims to determine the effect between variables, namely regarding entrepreneurial literacy and creative thinking skills on students' interest in entrepreneurship in students majoring in PIPS and PMIPA class of 2019, University of Jambi. This research is a quantitative research. The population in this study were students majoring in PIPS and PMIPA class of 2019 with a total of 243 respondents. The data collection technique was carried out by distributing the Google link via the WhatsApp group which contained a research questionnaire to the respondents. The data analysis technique used is multiple linear regression analysis with the help of the SPPS 22.0 for windows program. The results of this study indicate that there is a mutual influence between entrepreneurial literacy and the ability to think creatively on the interest in entrepreneurship. The Entrepreneurial Literacy variable (X1) has a tcount value of 4.645 greater than ttable or 4.645 > 1.651 with a positive sign at sig 0.000 <0.05. And from the calculation of the Creative Thinking Ability variable (X2) it has a tcount of 6.302 which is positive, while ttable can be obtained ttable 1.651, because the tcount value is 6.302 greater than ttable or 6.302 > 1.651. Based on the results of the F test with an SPSS calculation of 22.0, it can be seen that the Fcount value is 24.661 while the Ftable is 3.033, so H0 is rejected and Ha is accepted, so that there is a significant influence between entrepreneurial literacy and the ability to think creatively on entrepreneurial interest.